2019
DOI: 10.1029/2018gh000142
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Clinical Respiratory Outcomes and Ambient Wildfire Smoke Exposure Among Pediatric Asthma Patients at National Jewish Health, 2012–2015

Abstract: Wildfires are a growing threat in the United States. At a population level, exposure to ambient wildfire smoke is known to be associated with severe asthma outcomes such as hospitalizations. However, little work has been done on subacute clinical asthma outcomes, especially in sensitive populations. This study retrospectively investigated associations between ambient wildfire smoke exposure and measures of lung function and asthma control, Forced Expiratory Volume in 1 Second (FEV1) and the Asthma Control Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 64 publications
0
50
0
2
Order By: Relevance
“…However, it is also possible that patients with asthma change their behavior in other ways that would ameliorate the harmful effects of wildfire smoke, such as increasing their use of rescue medications. Lipner et al [32] observed that lung function in children aged 12-21 years initially decreased following a smoke exposure event (at a 1 day lag) but subsequently increased to above normal (at a 2 day lag). They speculated that this was due to older children effectively managing their symptoms using rescue medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that patients with asthma change their behavior in other ways that would ameliorate the harmful effects of wildfire smoke, such as increasing their use of rescue medications. Lipner et al [32] observed that lung function in children aged 12-21 years initially decreased following a smoke exposure event (at a 1 day lag) but subsequently increased to above normal (at a 2 day lag). They speculated that this was due to older children effectively managing their symptoms using rescue medications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there appears to be factors other than increased PM concentration that contribute to the increased harmfulness of wildfire smoke. More research is needed to understand these factors, but current research suggests that the harmfulness of wildfire PM may be affected by fuel source and burn rate [24], ambient temperature [26], behavioral changes [31][32][33], and smoke transport distance [23].…”
Section: Discussionmentioning
confidence: 99%
“…Wildfire smoke PM 2.5 and non-smoke PM 2.5 were jointly characterized using a previously published method [28] that has been used in a prior health study [29]. This method combines NOAA’s satellite imagery-based Hazard Mapping System [30,31,32] to determine daily smoke plume extent with spatial interpolation of ground-based PM 2.5 monitor values downloaded from the US EPA Air Quality System (AQS).…”
Section: Methodsmentioning
confidence: 99%
“…Lipner et al [32] observed that lung function in children aged 12-21 initially decreased following a smoke exposure event (at a 1 day lag) but subsequently increased to above normal (at a 2 day lag). They speculated that this was due to older children effectively managing their symptoms using rescue medications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there appears to be factors other than increased PM concentration that contribute to the increased harmfulness of wildfire smoke. More research is needed to understand these factors, but current research suggests that the harmfulness of wildfire PM may be affected by fuel source and burn rate [24], ambient temperature [26], behavioral changes [31][32][33], and smoke transport distance [23]. Tables Table 1 -Daily mean, range, and standard deviation for asthma visits, PM, and weather factors.…”
Section: Discussionmentioning
confidence: 99%